The interval symmetric single-step ISS1 procedure for simultaneously bounding simple polynomial zeros - Monsi, Mansor (Institute for Mathematical Research, Universiti Putra Malaysia, 2011)
The interval single-step procedure IS1 established by Alefeld and Herzberger (1983) has been modified. The idea of Aitken (1950) and Alefeld (1977) is used to establish the interval symmetric single-step procedure ISS1.This procedure has a faster convergence rate than does IS1. In this paper, the convergence analysis of the procedure ISS1using interval arithmetic (Moore (1962, 1979), Alefeld and Herzberger (1983)) is shown. The procedure ISS1is considered as the interval version of the point symmetric single-step procedure PSS1 Monsi (2010).